IMPLEMENTASI PERATURAN DAERAH KOTA MAKASSAR NOMOR 5 TAHUN 2022 TENTANG PERLINDUNGAN GURU DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Wanda, Riswanda; Jamil (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
This research is to: 1) determine the control the procedures for handling legal protection for teachers in Makassar City; 2) understand teacher protection from the perspective of siyasah syar’iyya. In an effort to answer this problem, we use descriptive qualitative research with several approaches, namely an empirical juridical approach and a Sharia normative approach. The data sources used in this research were primary data sources from interviews with the Head of Legal Division at the Regional Secretariat of Makassar City, GTK Staff (Certification Process Administrators) at the Education Service, PGRI Foundation Management, and Chair of the Indonesian Ulema Council of Makassar City. Secondary data sources are books, journals and previous research results. Data collection techniques through observation, interviews and documentation. The following research results were obtained: 1) Procedures for handling legal protection for teachers through mediation efforts if there is no criminal act, if a criminal act occurs then the resolution is carried out by law enforcement officials; 2) The siyasah syar’iyyah perspective views that Regional Regulation Number 5 of 2022 is in accordance with the concept that regulations must be made for the interests and benefit of the people. In Islam, teachers are defined as a very noble profession because they provide knowledge about Islam and also teach a person’s morals according to the teachings of the prophets, so they must be given protection from the government.